ORAL REHABILITATION WITH COMPLETE DENTURES VERSUS OVERDENTURES ON IMPLANTS: A NARRATIVE REVIEW - Maria Bolat; Raluca Elena Baciu; Zenaida Surlari; Dana Gabriela Budala; Bogdan Bulancea; Doriana Agop-Forna; Dan Nicolae Bosînceanu; Ionuț Luchian (Romanian Dental Association for Education, 2022)
Introduction. Many alternatives exist for treating total edentulism, including conventional complete dentures (CCD), implant-supported overdentures, and implant-supported fixed prostheses. Complete dentures have been the standard prosthodontic therapy for people who are edentulous for quite some time. The majority of denture-wearing edentulous patients are pleased with their prostheses, but some people just can't get used to them, and it seems that the level of clinical and technical expertise involved or the quality of the tissues supporting the dentures have little effect on how happy those people are with their results. While the routine prescription of an overdenture supported by two or even one implant for an edentulous mandible is becoming the standard of care in many developed nations, this treatment option is out of reach for the majority of the world's poor, who often cannot afford even "low-tech" therapies like conventional dentures.